Petrogenesis of the Kuangshancun and Hongshan intrusive complexes from the Handan–Xingtai district: Implications for iron mineralization associated with Mesozoic magmatism in the North China Craton. (1st December 2015) - Sun, Yi; Xiao, Long; Zhan, Qiongyao; Wu, Jianxun; Zhu, Dan; Huang, Wan; Bai, Ming; Zhang, Yanhai
Highlights: Kuangshancun and Hongshan complexes formed at around 135 Ma. Ore-bearing and ore-barren intrusions display similar geochemical characteristics. They originated from an enriched mantle source, but experienced distinct magmatic processes. High oxidation states and water contents could be considered as key factors that led to the iron mineralization. Abstract: The Handan–Xingtai district in eastern China exposes numerous late Mesozoic intrusions. Among these, the Kuangshancun intrusive complex is one of the major ore-related intrusions whereas the Hongshan complex is barren, although both intrusions display similar geochemical characteristics. The Kuangshancun complex consists of diorite and monzonite, with zircon LA-ICP-MS U–Pb age of 133.7 ± 1 Ma. The Hongshan complex mainly consists of syenite and shows zircon U–Pb age of 134.5 ± 1 Ma. The mineral chemistry of plagioclase from both complexes reveals normal zoning, consistent with the fractional crystallization process. Rocks of the Kuangshancun complex show SiO2 in the range of 58.92–63.84 wt.%, Na2 O of 4.63–8.81 wt.%, and Al2 O3 of 16.14–18.18 wt.%, together high Sr/Y (14–54) and high LaN /YbN (8.30–16.18) ratios. They show enrichment in LREE and depletion in HREE and HFSE, with no remarkable Eu anomalies, similar to the features of adakites. The whole rock initial 87 Sr/ 86 Sr ratios range from 0.706661 to 0.706722 and ε Nd ( t  = 134 Ma) between −15.26 and −15.12, which are consistent with zircon 176 Hf/ 177 Hf ratios of 0.281940–0.282059 and ε Hf ( t ) values of −27.0 to −22.7. Samples of the Hongshan complex show SiO2 in the range of 56.57–68.16 wt.%, high Sr/Y (19–112) and high LaN /YbN (11.39–16.82) ratios. The zircon ε Hf ( t ) values are in the range of −15.9 to −12.8 and ε Nd ( t  = 134 Ma) is between −9.82 and −8.62. The Kuangshancun complex was derived through partial melting of an enriched lithospheric mantle contaminated by lower continental crust components. The Hongshan complex was also derived from the EM I-like mantle source. However, the calculated zircon Ce 4+ /Ce 3+ and Eu/Eu ∗ ratios indicate that the source magma of the Kuangshancun complex were characterized by higher oxygen fugacity as compared to that the Hongshan complex. The high oxidation states and high water contents are considered as possible key factors that led to the iron mineralization in the Kuangshancun and other intrusions in the Handan–Xingtai district.